Enhanced Nucleation of Lysozyme Using Inorganic Silica Seed Particles of Different Sizes - Weichsel, Ulrike; Segets, Doris; Janeke, Stefanie; Peukert, Wolfgang (Crystal Growth and Design, 2015)
In this work we investigate the impact of differently sized plain silica nanoparticles (NPs) between 10 and 200 nm on the crystallization of lysozyme (LSZ). In the first part of our work we investigate the electrostatic interactions between LSZ and NPs by zeta potential measurements and place special emphasis on the adsorption behavior of LSZ@SiO2. The determined adsorption isotherms - derived from UV-vis spectroscopy - indicate that with increasing particle size more LSZ is adsorbed per NP surface area probably due to a size-dependent surface chemistry and the variation of surface curvature. Second, seeded crystallization experiments both at the microliter and milliliter scale and thus close to a technically relevant scale were performed. A clearly extended crystallization window upon the addition of seed particles toward lower protein and salt concentrations was found. Moreover, induction times of crystal formation and crystallization times were considerably reduced. These effects were intensified with the addition of larger seed particles. In general, with the addition of silica seed particles, a shift of the final crystal size distribution to larger structures is observed.